Group-Specific Monitoring of Phenol Hydroxylase Genes for a Functional Assessment of Phenol-Stimulated Trichloroethylene Bioremediation - Futamata, Hiroyuki (American Society for Microbiology, 2001)
The sequences of the largest subunit of bacterial multicomponent phenol hydroxylases (LmPHs) were compared. It was found that LmPHs formed three phylogenetic groups, I, II, and III, corresponding to three previously reported kinetic groups, low-K(s) (the half-saturation constant in Haldane's equation for trichloroethylene [TCE]), moderate-K(s), and high-K(s) groups. Consensus sequences and specific amino acid residues for each group of LmPH were found, which facilitated the design of universal and group-specific PCR primers. PCR-mediated approaches using these primers were applied to analyze phenol/TCE-degrading populations in TCE-contaminated aquifer soil. It was found that the aquifer soil harbored diverse genotypes of LmPH, and the group-specific primers successfully amplified LmPH fragments affiliated with each of the three groups. Analyses of phenol-degrading bacteria isolated from the aquifer soil confirmed the correlation between genotype and phenotype. Competitive PCR assays were used to quantify LmPHs belonging to each group during the enrichment of phenol/TCE-degrading bacteria from the aquifer soil. We found that an enrichment culture established by batch phenol feeding expressed low TCE-degrading activity at a TCE concentration relevant to the contaminated aquifer (e.g., 0.5 mg liter(−1)); group II and III LmPHs were predominant in this batch enrichment. In contrast, group I LmPHs overgrew an enrichment culture when phenol was fed continuously. This enrichment expressed unexpectedly high TCE-degrading activity that was comparable to the activity expressed by a pure culture of Methylosinus trichosporium OB3b. These results demonstrate the utility of the group-specific monitoring of LmPH genes in phenol-stimulated TCE bioremediation. It is also suggested that phenol biostimulation could become a powerful TCE bioremediation strategy when bacteria possessing group I LmPHs are selectively stimulated.